1989
DOI: 10.1177/002199838902300706
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Paris Equation to the Fatigue Growth of Transverse Ply Cracks

Abstract: A model based on a stress intensity factor for a growing transverse ply crack is outlined. The model is applied to experimental observations of crack growth in a trans parent 0/90/0 glass fibre/epoxy laminate under fatigue loading. The crack growth rate is found to be independent of crack length but to depend on the spacing between cracks. Under static loading and fatigue loading at high maximum stress, cracks grow by fast frac ture. Slow crack growth is observed at lower maximum fatigue stresses and in the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(30 citation statements)
references
References 25 publications
3
27
0
Order By: Relevance
“…The CGR results are plotted against the computed ERR for an isolated crack front in Figure 10(b). A large variance in the data is observed, and the magnitude of the variance is seen to be approximately the same as found in [25]. The large degree of scatter in the dataset indicates that a single Paris' Law relationship is not sufficient to describe the physics of crack propagation.…”
Section: Crack Growth Rate (Cgr)mentioning
confidence: 68%
See 2 more Smart Citations
“…The CGR results are plotted against the computed ERR for an isolated crack front in Figure 10(b). A large variance in the data is observed, and the magnitude of the variance is seen to be approximately the same as found in [25]. The large degree of scatter in the dataset indicates that a single Paris' Law relationship is not sufficient to describe the physics of crack propagation.…”
Section: Crack Growth Rate (Cgr)mentioning
confidence: 68%
“…Crack growth rates (CGR) for the stable propagation of off-axis cracks under CA loading with constant load ratio have been reported in [8,9,18,25]. In [8,25] the CGR of off-axis cracks throughout the fatigue test were manually measured and it was found that the CGR were independent of crack length but dependent on stress level and crack density.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cracks are usually through cracks InF2.ning that they progress rapidly across the entire width of the specimen and it is generally accepted that they are the first failure mode to occur with rising load, beginning as early as 30% of ultimate load. Keen interest in TMC in polymeric composites was found in the mechanics of composites literature through the 1980s [1][2][3][4][5][6][7] and this stimulated measurements ofTMC using acoustic emission techniques.…”
Section: Introductionmentioning
confidence: 99%
“…• as observed classically in fatigue tests ( [17][18][19][20][21]), microcracks develop first near the edge of the sample until saturation of the microcracking rate. Then, cracks propagate from the edge toward the core.…”
mentioning
confidence: 96%